Challenging the empire in empir(e)ical research: the question of speaking in music education. (20th October 2018) - Hess, Juliet
ABSTRACT: As an enterprise, academic research is in the business of knowledge production—a practice through which researchers continually engage in speaking for or about others. This paper explores the colonial potential of research and ethnography in particular. I draw on Alcoff's framework (Alcoff, L. M. 1991. "The Problem of Speaking for Others." Cultural Critique 20 (Winter, 1991–1992): 5–32) to consider issues inherent in speaking for Others and mobilise Critical Race Theory (CRT) and anti-colonialism as tools and lenses to examine research activities with the goal of moving toward more ethical and productive outcomes. The next portion of this paper puts forward ways to guard against coloniality in research. I rethink Alcoff's caveats through these critical lenses alongside considering possible anti-colonial methodologies. I then consider the way these dynamics operate in my own research and conclude with a number of implications for music education researchers to help us shift our research toward a more ethical, reciprocal, anti-colonial research praxis.